2011
DOI: 10.1016/j.applthermaleng.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Critical investigation of heat transfer enhancement using nanofluids in microchannels with slip and non-slip flow regimes

Abstract: The Reynolds number in nanofluids studies depends on the inlet velocity and the kinematic viscosity of nanofluid. The nanofluid kinematic viscosity increases with an increasing in nanoparticles volume fraction while the inlet velocity should be increased to keep the Reynolds number constant. Therefore, it is not clear that either increasing the nanoparticles volume fraction or increasing the inlet velocity has major role on heat transfer enhancement in nanofluids flow studies which are done at constant Reynold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…The nanofluids are more stable and have acceptable viscosity and better wetting, spreading, and dispersion properties on solid surface [3,4]. The characteristic feature of International Journal of Engineering Mathematics nanofluids is thermal conductivity enhancement, a phenomenon observed by Masuda et al [5].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The nanofluids are more stable and have acceptable viscosity and better wetting, spreading, and dispersion properties on solid surface [3,4]. The characteristic feature of International Journal of Engineering Mathematics nanofluids is thermal conductivity enhancement, a phenomenon observed by Masuda et al [5].…”
Section: Introductionmentioning
confidence: 89%
“…As such, the Rosseland model, while limited compared with other flux models, can simulate to a reasonable degree of accuracy thermal radiation in problems ranging from thermal radiation transport via gases at low density to thermal radiation simulations associated with nuclear blast waves. If the temperature differences within the flow are sufficiently small, then (12) can be linearized by expanding 4 into the Taylor series about ∞ , which after neglecting higher-order terms takes the form…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Some other researchers recognized that the boundary layer, especially the velocity-slip and temperature-jump at fluid-solid interface in a microchannel influenced heat transfer enhancement even more significantly ( Hettiarachchi, H.D.M., 2008, Vajravelu, K., 2011,Vandadi, V., 2011, Akbarinia, A., 2011, Aminreza, N., 2012. Hettiarachchi et al(2008) numerically studied 3D laminar slip-flow and heat transfer in a rectangular microchannel with constant wall temperature and found that the local Nusselt number increased with the increased slip-velocity and the decreased jump-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Vandadi et al(2011) took into account the effect of velocity slip, temperature jump and viscous dissipation term, and the results showed that the viscous dissipation effect on heat transfer in microchannels is significant and should not be neglected. Akbarinia, et al (2011) investigated forced convection of Al2O3-water nanofluid flows in two-dimensional rectangular microchannels for heat transfer enhancement. It was found that viscous dissipation is beneficial to the heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it is prudent to combine base uids with nanoparticles to achieve both the characteristics of a base uid and the physical properties of the nanoparticles [2,3]. Suspending nanoparticles a ects the base uid's homogeneity and the randomness of molecular motion leading to higher conductive rates and better convective heat transfer performances compared to base uids [4][5][6][7]. There are however mechanisms, which include particle agglomeration, particle shape/surface area, nanoparticle size, temperature and liquid layering on the nanoparticle liquid interface that still need to be fully understood.…”
Section: Introductionmentioning
confidence: 99%